Altitude/hypoxic training for endurance athletes - Millet, G.; Brocherie, F. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
Since the early overview article of Randall Wilber and the characterization of three main types of altitude/hypoxic training (live high-train high, LHTH; live high-train low, LHTL; and live low-train high, LLTH), many variations of these types have been described in the last 15 years: FIrst, we proposed a new combination of hypoxic methods (live high-train low and high, LHTLH) associating LHTL (sleeping between 2,500 and 3,000 m) with training near sea-level except for a new (2-3 per week) LLTH high-intensity sessiongs) at altitude; second, the development of different types of LLTH methods (e.g. RDH, repeated sprint training in hypoxia or RTH, resistance training in hypoxia originally dedicated for team- or racket sports - see Chapter 17) let to a widening (or maybe a sophistication) of the available methods (see Figure 16.1 for the panorama of all methods currently proposed).